2019
DOI: 10.1123/japa.2018-0309
|View full text |Cite
|
Sign up to set email alerts
|

Low-Volume High-Intensity Interval Training Versus Moderate-Intensity Continuous Training on Body Composition, Cardiometabolic Profile, and Physical Capacity in Older Women

Abstract: Objectives: To compare the effect of low-volume high-intensity interval training (HIIT) with moderate-intensity continuous training (MICT) on fat mass, cardiometabolic profile, and physical capacity, and confirm its feasibility in older women. Methods: Inactive older women (60–75 years) were randomly assigned to 8 weeks of either HIIT (75 min/week; n = 9) or MICT (150 min/week; n = 9). Body composition, fasting metabolic profile, cardiovascular risk (Framingham score), and physical capacity (senior fitness tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 59 publications
9
40
1
2
Order By: Relevance
“…These results contradict our hypothesis because we expected that the higher velocities achieved in the HIIT condition would promote greater increases in gait velocity due to specificity and following previous findings [42]. On the other hand, our data is not without support, since there is evidence in which the performance of HIIT or MICT promoted functional performance gains, but without differences between the types of training [43][44][45]. Considering the characteristics of the participants, these functional gains are very important, since they can decrease the risk of mortality, in which higher levels of functional capacity are related to lower risk of falls and mortality [46,47].…”
Section: Discussioncontrasting
confidence: 98%
“…These results contradict our hypothesis because we expected that the higher velocities achieved in the HIIT condition would promote greater increases in gait velocity due to specificity and following previous findings [42]. On the other hand, our data is not without support, since there is evidence in which the performance of HIIT or MICT promoted functional performance gains, but without differences between the types of training [43][44][45]. Considering the characteristics of the participants, these functional gains are very important, since they can decrease the risk of mortality, in which higher levels of functional capacity are related to lower risk of falls and mortality [46,47].…”
Section: Discussioncontrasting
confidence: 98%
“…Therefore, there seems to be a greater trend for VO 2max -ES improvement in HIIT than in MICT. Our results are in accordance with various studies showing that the application of both HIICT and MICT succeeded in increasing the VO 2max values for subjects with cardiovascular diseases [4,24], as well as in healthy elderly and middle-aged people [38]. Similarly, in line with the better trend shown by HIICT, a meta-analysis showed that HIIT improved VO 2max more than MICT in overweight or obese adults [39].…”
Section: Discussionsupporting
confidence: 92%
“…They reviewed the effects of 12 weeks' HIIT on the serum lipid profile of patients with dyslipidemia and concluded that HIIT could be used as an intervention method to regulate the serum lipids of dyslipidemia patients (17). Also, the findings of the present study are in line with the findings by Boukabous et al (18). They reported that two types of training, including HIIT and moderate-intensity continuous training (MICT) improved lipid profile and fasting blood glucose in older women (18).…”
Section: Discussionsupporting
confidence: 93%
“…Also, the findings of the present study are in line with the findings by Boukabous et al (18). They reported that two types of training, including HIIT and moderate-intensity continuous training (MICT) improved lipid profile and fasting blood glucose in older women (18). In addition to exercise activities, nutritional therapy is an essential part of treatment for people with high blood lipids.…”
Section: Discussionsupporting
confidence: 92%